INCREASING THE ENTREPRENEURIAL CAPACITY OF BUMDES MANAGEMENT IN BAJENG DISTRICT, GOWA REGENCY SOUTH SULAWESI - Hatma, Ramli; Thamrin, Muhammad; Gempita, Gempita; Fadly, Hery (Journal of Entrepreneur, Business and Management, 2024)
This service aims to increase the entrepreneurial capacity of BUMDesa administrators in Bajeng District through Management, Entrepreneurship, Marketing and Bookkeeping Training. To increase capacity in the field of management, participants were given training on how management functions that we know as POAC (planning, organizing, actuating, controlling) can be carried out properly in managing the resources owned so that organizational goals can be achieved effectively and efficiently. To increase capacity in the field of entrepreneurship to the trainees, material was given about: (1) entrepreneurial mentality, namely how to build a mental attitude that entrepreneurial actors must have so that they can compete in their business development (2) creative thinking, where BUMDes administrators must be able to take advantage of existing business opportunities by utilizing their resources (3) business management, each BUMDes administrator understands the analysis of the micro environment that affects (Competitor, New Entry, Buyer, Supplier), Product Life Cycle consisting of Introduction, Growth, Maturity, Decliner as a tool for justifying the business stages managed and being able to set the right strategy at each of these stages (4) Business Plan, Bundes Management is able to make a good business plan by considering the condition of the resources owned from the internal side and the opportunities and threats that exist from the side External    To increase capacity in the field of marketing, the trainees were given material on how to determine effective marketing strategies used to increase sales turnover by utilizing the marketing mix consisting of 4P, namely: (1) product development in accordance with consumer tastes, (2) determination of competitive product selling prices (prices) in accordance with people's purchasing power, (3) choosing the right distribution channel (plice) so that poduk (4) choosing the right promotion mix in delivering information about the product to consumers   For capacity building in the field of bookkeeping, the trainees were given an understanding of bookkeeping that can be applied in managing their business finances, with the following materials: (1) Accounting, providing an understanding of the basic equation of accounting which is a balance between the asset and asset sides, (2) Calculating and recording in bookkeeping, aiming for business actors to know the financial condition of the business they runKeywords: BUMDesa, Management, Entrepreneurship, Marketing, Bookkeeping.